Domenico Cotugno (1736-1822), Antonio Scarpa (1752-1832), and Alfonso Corti (1822-1876): The Most Important Discoveries of the Inner Ear Made by Young Italian Physicians—Domenico Cotugno - Colombo, Anna; Di Pasquale Fiasca, Valerio Maria; Cozza, Andrea; Martini, Alessandro (ENT Updates, 2023)
The 18th and 19th centuries bequeathed to modern science fundamental discoveries in microscopic anatomy. The most important findings regarding the ear were made by young Italian researchers: Domenico Cotugno, Antonio Scarpa, and Alfonso Corti. Domenico Cotugno was born in Ruvo di Puglia on January 29, 1736, into a modest family. He was only 24 years old when his first great work, De aquaeductibus auris humanae internae anatomica dissertatio, was published in 1760. Cotugno, who worked on fresh ear specimens collected from newborns or fetuses, discovered the existence of 2 aqueducts (Cochlear and vestibular). Thanks to his revolutionary dissection technique, he also detected the constant presence of labyrinthic fluid. He wrote that the aqueducts were filled with liquid and not with air, as was generally held according to the Aristotelian dogma of aer ingenitus, uncontested by scholars such as Falloppio, Eustachi, and Willis. Cotugno also stated that the perilymphatic and subarachnoid spaces communicated at the base of the brain. His theory of resonance and his description of anatomical ear structures laid the foundations of today’s comprehension of hearing.